Intermittent Physical Training Decreases Peak of Blood Glucose Level after Meals in Rats - Eka Arum Cahyaning Putri (Scitepress, 2017)
Abstract: Some people prefer doing exercise following the intermittent model while others prefer the continuous one . However, it is still unclear which is the best one for blood glucose regulation. This study was carried out to determine the difference between the changes in blood glucose levels after doing physical exercise for the intermittent and the continuous model. The subject was male adult rats divided into 3 groups: control, continuous, and intermittent, 5 rats in each group. The rats swam in moderate intensity every day for 8 weeks. The results showed that the control group had the highest results of the peak (30 minutes) blood glucose levels after meals followed by the other 2 groups The results of the intermittent group had a significant peak in blood glucose levels 30 minutes after meals (p <0.05). Also the differences in blood glucose 30 minutes and 60 minutes after meals in the intermittent and continuous groups were significantly different than the control group (p <0 .05). During the 8 weeks of moderate physical exercise every day, it can be assumed that there was more insulin secretion to reduce peak blood glucose levels after meals. The lower blood glucose difference at 30 minutes and 60 minutes after meals of both the continuous and intermittent groups compared with the control group indicates that glucose uptake by cells is better in those groups . In conclusion, our data support the benefit of intermittent and continuous exercise training for the optimal regulation of blood glucose levels. The intermittent model also has more effect on the peak phase of blood glucose level after meals.